THE EFFECT OF USING INTERACTIVE GUESSING GAME TECHNIQUE ON FLUENCY STUDENT’S SPEAKING SKILL - Puspitasari, Zully Zulaikho; Asari, slamet (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2018)
This article explains the result of research that aim to test whether using interactive guessing game technique give significant effect on fluency student’s speaking skill in short functional text of MTs. Bustanul Ulum Tanggungprigel. This research uses a quasi experimental research design. The population of this research was the VIII grade students of MTs. Bustanul Ulum Tanggungprigel. There were two classess that totalized 50 students. The sample of this research was VIII A and VIII B. The sample was selected by population sampling technique. The instruments were speaking test. The data were analyzed by independent sample t-test formula. The result of this research were the implementation of using interactive guessing game was significant to improve fluency student’s speaking skill. It can be conclude that interactive guessing game technique gave significant effect toward fluecny student’s speaking skill at MTs. Bustanul Ulum Tanggungprigel.